IMPROVED CIPROFLOXACIN PENETRATION IN GOAT EYES USING COMPLEXATION TECHNIQUE - DURGA PANDEY; DEEPTI JAIN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present work was to improve the retention and penetration of ciprofloxacin (CF) ion pair entrapped within submicron emulsion (SE) in goat eyes and characterize the SE for improvement of ocular activity. The developed delivery system resulted with prolonged drug release as compared to the conventional dosage form. Methods: SE prepared by high-energy emulsification and sonication to obtain uniform globule size. Ion-pair complex is prepared by precipitation method. Results: Average internal droplets size of the optimized formulation was 0.300 μm, pH of the optimized formulation was 6.4±0.7 (average of three determinations) and viscosity 3.2±0.3 cP suitable for ocular use. Entrapment was 92.12%. In vitro drug release pattern in dialysis membrane showed sustain release of CF, a cumulative percent release of CF was found 77% in 10 h. Scanning electron microscopy showed spherical shape and size within 1 μm. In vitro release in goat eyes was found 35.86 % for optimized formulation compared to market, 26.83% in 60 min. Conclusion: Developed optimized formulation can be a good candidate for ocular drug delivery in severe ocular infections where frequent dosing required such as endophthalmitis, corneal ulcer, and penetrating trauma.